PENERAPAN PRINSIP-PRINSIP E-PROCUREMENT DI BAGIAN PENGADAAN BARANG/JASA SEKRETARIAT DAERAH KOTA SAMARINDA - Teten Teten (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This research is to describe, analyze and interpret the Implementation of Procurement Principles in the Goods / Services Procurement Section of the Samarinda City Regional Secretariat through a research focus: effective, efficient, transparent, open, competitive, fair, and accountable, as well as to find out what are the supporting factors and the barrier. Collecting data through observation, interviews and documentation. The results showed that the principles of efficiency, effectiveness still need to be improved, the principles of transparency, openness have worked well. The principle of competition, fairness, is still an indication of intervention. The application of the accountable principle requires better archive management to facilitate auditing.Keyword : e-government, e-procurement, atransparent, accountable